(untitled) (Research, Society and Development, 2022)
Mental health is one of the most neglected areas of public health. Due to limited access, few people around the world have access to quality mental health services. The use of medicinal plants and herbal medicines for the treatment, cure and prevention of diseases is one of the oldest forms of therapy. The use of these therapies for the treatment of anxiety disorders has great current prominence in the COVID-19 pandemic, causing a search for such alternative methods. Pharmaceutical care (PA) within the scope of phytotherapy must occur actively, taking part in the design of medicinal plants and herbal medicines, in the promotion of their rational use. The study aimed to present the main medicinal and herbal plants used in the treatment of anxiety disorder and to assess the importance of PA in its safe and rational use, with an emphasis on health promotion, involving PA and user education. A Bibliographic Review was carried out on Google Scholar and VHL, indexed in the LILACS, MEDLINE and SciELO databases, from 2010 to 2021, in Portuguese. In this review, we observed that medicinal plants such as P. methysticum L., V. officinalis and P. incarnata were the most investigated species in previous studies. Medicinal plants are of great interest to the population, as their use is a cultural practice. Therefore, future studies with pre-clinical analyzes and more diagnoses aimed at people with anxiety disorder who use medicinal plants and herbal medicines as treatment are necessary.